2022
DOI: 10.3389/fnut.2021.818290
|View full text |Cite
|
Sign up to set email alerts
|

Effects of M/G Ratios of Sodium Alginate on Physicochemical Stability and Calcium Release Behavior of Pickering Emulsion Stabilized by Calcium Carbonate

Abstract: The gel properties of sodium alginate (SA) have been revealed to be strongly correlated with its ratio of D-mannuronate to L-guluronate (M/G ratio). Herein, we focused on SA with different M/G ratios to conduct an in-depth study on the effect of the M/G ratio difference on physicochemical stability and calcium release behavior of the Pickering emulsion stabilized by calcium carbonate (CaCO3). The oil phase was added to the aqueous phase, prepared by SA with different M/G ratios (2.23, 0.89, and 0.56) and CaCO3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 40 publications
(45 reference statements)
0
4
0
Order By: Relevance
“…25 We used alginates with different G/M ratios to best match the stiffness of soft tissues. 38 With this strategy we demonstrated that high M alginates (A4) form softer hydrogels with properties similar to brain tissue stiffness and that are also suitable for diffusion of blood components.…”
Section: Biomaterials Science Papermentioning
confidence: 99%
“…25 We used alginates with different G/M ratios to best match the stiffness of soft tissues. 38 With this strategy we demonstrated that high M alginates (A4) form softer hydrogels with properties similar to brain tissue stiffness and that are also suitable for diffusion of blood components.…”
Section: Biomaterials Science Papermentioning
confidence: 99%
“…The physicochemical properties of alginate depend on the M/G ratio [25], the block length, and the arrangement of repeating units in the biopolymer [26]. Therefore, the physicochemical properties of alginate can be influenced by where the extracted seaweed is grown and the season of harvesting.…”
Section: Molecular Structure and Properties Of Alginate And Hyaluroni...mentioning
confidence: 99%
“…The particles that can be used as Pickering emulsion stabilizers come from a wide range of sources, including inorganic particles, synthetic particles, and organic particles. Inorganic particles are the earliest stabilizers used in Pickering emulsions, including clay [ 16 ], calcium carbonate [ 17 ], silica [ 7 , 18 , 19 ], etc. Synthetic particles include various synthesized polymers [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%